Solid pseudopapillary neoplasm of the pancreas after living-donor liver transplantation - Shoichi Tsuzaka; Norio Kawamura; Takuya Harada; Takuji Ota; Yoshikazu Ganchiku; Masaaki Watanabe; Ryoichi Goto; Hirofumi Kamachi; Toshiya Kamiyama; Tsuyoshi Shimamura; Nanase Okazaki; Tomoko Mitsuhashi; et al. (Journal of Pediatric Surgery Case Reports, 2023)
Background: Solid pseudopapillary neoplasm of the pancreas has been classified by the World Health Organization as a low-grade malignant tumor with potential to metastasize. The standard treatment for this neoplasm is complete surgical resection. However, it is not always feasible to perform a complex procedure such as pancreaticoduodenectomy or distal pancreatectomy, especially for patients with a history of hepato-biliary-pancreatic surgery. In such cases, the treatment strategy must consider the patient's postoperative quality of life. We herein report a case of solid pseudopapillary neoplasm of the pancreas following living-donor liver transplantation. Case presentation: The patient was a 13-year-old girl who had undergone the Kasai procedure for biliary atresia at 140 days of age. She thereafter underwent living-donor liver transplantation because of recurrent cholangitis and progressive jaundice. Her repeated history of cholangitis had caused narrowing of the portal vein. Therefore, the portal vein was reconstructed using the donor's ovarian vein as an interposition graft. At 13 years of age, a mass was identified at the head of the pancreas. Biopsy was performed and the patient was diagnosed with solid pseudopapillary neoplasm of the pancreas. Surgical resection was planned, and three options were considered: pancreaticoduodenectomy, duodenum-preserving pancreatic head resection, and enucleation. Considering the complications associated with radical surgery, tumor enucleation was performed. The patient developed a postoperative pancreatic fistula that required prolonged fasting and drainage. She began a low-fat diet on postoperative day 15. Because the pancreatic fistula was well controlled with a low-fat diet, the patient was discharged on postoperative day 51 after she and her parents had received dietary guidance. At the time of this writing, 1 year had passed since the enucleation with no evidence of recurrence. Conclusions: We have herein reported a case of solid pseudopapillary neoplasm of the pancreas after living-donor liver transplantation. Although a radical operation such as pancreaticoduodenectomy or distal pancreatectomy is preferable from an oncological perspective, enucleation should be considered for patients with high surgical risk.